The tinkerer's accomplice : how design emerges from life itself - Turner, J. Scott, 1951- (Harvard University Press, 2007)
Physiologist Scott Turner argues eloquently that the apparent design we see in the living world only makes sense when we add to Darwin's towering achievement the dimension that much modern molecular biology has left on the gene-splicing floor: the dynamic interaction between living organisms and their environment. Only when we add environmental physiology to natural selection can we begin to understand the beautiful fit between the form life takes and the way life works.